2005
DOI: 10.1016/j.asr.2005.01.075
|View full text |Cite
|
Sign up to set email alerts
|

Supernova remnant 1987A: The latest report from the Chandra X-ray Observatory

Abstract: We continue monitoring supernova remnant (SNR) 1987A with the Chandra Xray Observatory. As of 2004 January, bright X-ray spots in the northwest and the southwest are now evident in addition to the bright eastern ring. The overall Xray spectrum, Since 2002 December, can be described by a planar shock with an electron temperature of ∼2.1 keV. The soft X-ray flux is now 8 × 10 −13 ergs cm −2 s −1 , which is about five times higher than four years ago. This flux increase rate is consistent with our prediction base… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…Pursuant to this idea, we applied ACIS subpixel resolution software to the photon events ( Mori et al 2001), formed several high-resolution images of the R136 region from those events, reconstructed those images using a simple maximum likelihood algorithm (described below), and used the reconstructions to identify additional X-ray point sources in R136. Similar reconstructions have been performed on ACIS observations of SN 1987A (e.g., Park et al 2005) and gravitational lenses (e.g., Chartas et al 2004) and revealed subarcsecond spatial features that were confirmed in other wave bands and proved essential for understanding the X-ray emission of these targets.…”
Section: Source Detection and Characterization Methodsmentioning
confidence: 58%
“…Pursuant to this idea, we applied ACIS subpixel resolution software to the photon events ( Mori et al 2001), formed several high-resolution images of the R136 region from those events, reconstructed those images using a simple maximum likelihood algorithm (described below), and used the reconstructions to identify additional X-ray point sources in R136. Similar reconstructions have been performed on ACIS observations of SN 1987A (e.g., Park et al 2005) and gravitational lenses (e.g., Chartas et al 2004) and revealed subarcsecond spatial features that were confirmed in other wave bands and proved essential for understanding the X-ray emission of these targets.…”
Section: Source Detection and Characterization Methodsmentioning
confidence: 58%
“…Point source spectrum: Γ = 1.7 − 3.0, N H = 2 × 10 21 − 10 24 cm −2 are assumed. Based on the image taken on July 22, 2004, a point source upper limit at 3-10 keV is L x ≈ 5 × 10 33 −3 × 10 35 erg s −1 (Park et al 2005). A numerical approximation of MHD hypercritical accretion in SN1987A can help us to resolve this mystery.…”
Section: Introductionmentioning
confidence: 99%
“…From Oct 1999 until Jan 2004 the 0.5-2 keV X-ray flux of the SNR has increased by a factor of 5 and appears to be growing brighter exponentially (Park et al 2005). Even from the earliest Chandra observations, deconvolved ACIS images have shown a ring-like geometry.…”
Section: Sn 1987amentioning
confidence: 99%
“…Since launch, SN 1987A has been the focus of a series of repeated observations with Chandra (see Park et al 2005 and references therein). One goal of these observations is to detect the emergence of the X-ray flux from a newly born compact object.…”
Section: Sn 1987amentioning
confidence: 99%
See 1 more Smart Citation